Establishing an applied training session in metrology at an agricultural engineering school (CIRAD, Montpellier, France). (2nd December 2014) - Calchera, G.; Linck, O.; Bouniol, A.; Ricci, J.; Servent, A.; Grevesse, C.; Martin, L.
Abstract : As part of its training activities, SupAgro – Institut des Régions Chaudes (IRC), an agricultural engineering school in Montpellier, has introduced an applied training session in metrology for its students. This was undertaken by the CIRAD metrology platform in partnership with the agrifood technology platform of the Qualisud Joint Research Unit. The session comprises two hour workshops during which students can apply the basic notions required for metrological monitoring of the quantities "temperature" and "weight". To that end, standard weights, a temperature calibration device comprising a thermostatically controlled calibration oil bath (uncertainty at k = 2 of 0.14 °C) and a standard temperature probe with an accuracy of ±0.01 °C were made available to the technology platform by the CIRAD metrology platform. During practical work, these COFRAC calibrated instruments are used to check balances and, in particular, make students aware of the importance of parameters that might influence the temperature measurement of a thermostatically controlled bath (homogeneity, resolution and accuracy of the thermometers, measurement repeatability, etc.). To that end, the Qualisud team specifically adapted a water bath so as to be able to position several temperature probes at different places in the bath. Students have to acquire an approach that needs to take into account a particular measuring context. The teaching scenario of the training session is structured around these metrological checks proposed directly to the students. The training session takes place each year with 2nd year students on the SAADS 2/IAAS course "Sustainable Agriculture and Agrifood Systems in the South" at SupAgro in Montpellier.